Thoracoscopic hiatoplasty in congenital diaphragmatic hernia is safe and less invasive: a prospective propensity-matched short-term study - Klinke Petrowsky, Michaela; Martel, Richard; Weiß, Christel; Mohr, Christoph; Schaible, Thomas; Dietze, Nina; Hoffmann, Jana; Boettcher, Michael; Elrod, Julia (Pediatric surgery international, 2025)
Congenital diaphragmatic hernia (CDH) is a condition linked to neonatal morbidity, mortality, and gastroesophageal reflux. Traditional hiatoplasty via laparotomy or laparoscopy is complicated by abdominal adhesions from previous CDH repair. A thoracoscopic technique, avoiding abdominal preparation, was introduced to address these issues. This study evaluates its safety and efficacy in children with CDH.
Online veröffentlicht: 21. Oktober 2025
Gesehen am 12.01.2026